The mechanical design process - Ullman, David G. 1944- (McGraw-Hill series in mechanical engineering, 2010)
Combines a practical overview of the design process with case material and real-life engineering insights. This book conveys the 'flavor' of design, addressing both traditional engineering topics as well as real-world issues like creative thinking, synthesis of ideas, visualization, and teamwork in a practical manner.